Information systems implementation failure in Malaysian government hospitals: How change management helps? - Che Pa, Noraziah; Md Jasin, Noorhayati; Abu Bakar, Nur Azzah (Universiti Teknikal Malaysia Melaka, 2018)
Successful implementation of Information System (IS) in government hospitals is indeed a challenging task. Fail to prevent or control challenges of Information System (IS) implementation have led to the failure of its implementation.Government has invested a big amount of money on information system (IS) projects to improve service delivery in healthcare.However, several of them failed to be implemented successfully due to several factors. This article proposes how Change Management (CM) helps in preventing the failure of IS implementation, hence ensuring the success of it. This study starts by discovering challenges of IS implementation in government hospitals.Combination of extensive literature review and deep interview approaches were employed to discover these challenges.CM has been employed in designing a prevention model to cater the challenges. The model caters three main phases of implementation; pre-implementation, during implementation, and post-implementation by adopting CM practices of Lewin's, Kotter's and Prosci's CM model.Six elements of CM comprising thirteen sub-elements adopted from the three CM models have been used to handle CFFs of Human and Support issues; guiding team, resistance avoidance, IS adoption, enforcement, monitoring, and IS sustainability. Successful practice of the proposed mapping is expected to prevent CFFs to occur, hence ensuring a successful implementation of IS in the hospitals.The proposed model has been presented and successfully evaluated by the domain experts from the selected hospitals.The proposed model is believed to be beneficial for top management, IT practitioners and medical practitioners in preventing IS implementation failure among government hospitals towards ensuring the success implementation.